MECHANISM OF MODELING FINANCIAL FLOWS IN THE ECONOMY OF GEORGIA. GENERAL ASPECTS - Bakradze, Malkhaz (European Scientific Journal, ESJ, 2013)
Model calculations are carried out and allow us to conclude: • Modeling the current economic situation (taking into consideration external factors) showed that GDP - the annual increases of 2.3% - is guaranteed to be achieved without Government interference; • The model of the acceleration of the pace of economic growth without economic promotion will not be considered. Acceleration of the pace of the transition to the new investment policy, optional discrete invest in promising directions. There was no increase in the volume of public ownership. As a result of investments in shares of State may manage its own package, as well as sell it and compensate own expense; • The new investment policy must comply with the state and other sources in the future by investing guarantor, "Battery" role, first and foremost, in terms of reducing the investment risks. Of private capital, which is significantly smaller than in developed countries, large and long-term projects of participation in not constitute investment priorities. Foreign capital, as a rule, participates in investment projects only with the local equity, and often (if not always) is necessary in case of the state guarantor. The state is the best guarantee for equity participation; • Georgia's economic growth is dependent on the current conditions, first of all, external factors - the external debt and import structure of prices generated by their fiscal effect on the course of U.S. dollars. Population employment and income levels are substantially related to these factors. Hence, the investment process in the country will significantly contribute to employment growth, population growth and economy of budget revenues and more became independent from the influence of external factors.